Does it Matter What We Drink? Beverage Type Preference Predicts Specific Alcohol-Related Negative Consequences Among College Students. (12th May 2019) - Mochrie, Kirk D.; Ellis, Jordan E.; Whited, Matthew C.
Abstract: Background : College student substance use has been a problem for many years. In particular, heavy alcohol consumption can create issues with academics, social relationships, and overall functioning. Unitary measures of generic alcohol consumption (e.g., drinking frequency) are important predictors of alcohol-related negative consequences, but the small amount of specific-beverage research available suggests that assessing beverage type consumed may enhance prediction. Objectives : The purpose of the present study was to expand knowledge of alcoholic beverage preference in relation to negative consequences and confirm the factor structure of the RAPI proposed by Martens et al. (2007 ) in a college student sample. Methods: In addition, the present study expanded current knowledge by assessing beverage preference type in relation to specific negative consequences on the RAPI. Results : Results replicated the three-factor structure originally found by Martens et al. (2007 ). Moreover, results found that individuals consuming shots of liquor or alcohol mixed with caffeine reported higher overall RAPI scores and higher scores on the Abuse/Dependence and Personal Consequences factors but not the Social Consequences factor than those consuming mixed drinks, beer, or wine. Conclusions/Importance: This research might inform discussions with incoming college freshman about not only alcohol consumption and negative consequences but the dangers of drinking specific types of alcohol beverages such as shots and/or alcohol mixed with caffeine.